TESMIN is a Prognostic Biomarker Associated with Immunosuppression and Activated Cell Cycle in Lung Adenocarcinoma - Yao, Zhiyuan; Song, Peng; Dong, Yanting; Wu, Zhe; Kong, Weimao; Jiao, Wenjie (Current Medicinal Chemistry, 2025)
BackgroundThe Testis Expressed Metallothionein Like Protein (TESMIN) gene encodes highly conserved, cysteine-rich, low-molecular proteins that are activated by and have an affinity for heavy metal ions. Previous literature has shown its association with cancer. Nevertheless, no thorough bioinformatics analysis of TESMIN has been done yet in lung adenocarcinoma (LUAD).MethodsDifferential expression of TESMIN between cancer and normal tissues was confirmed by analyzing databases and immunohistochemistry staining. Enrichment analysis was adopted to explore biological functions. The relationship of TESMIN with immune infiltration was evaluated by ssGSVA, with immunotherapy response predicted by TCIA and TIDE tools, with mutational traits analyzed by R software. Drug sensitivity analysis was implemented via GSCA tool, pRRophetic algorithms, and CellMiner database.ResultsThe results demonstrated that TESMIN expression was upregulated in tumor tissue and related to Ki67. TESMIN was associated with poor survival and significantly related to age, gender, N stage, M stage, pathological stage, and survival status. TESMIN-related genes (TRGs) were primarily involved in cell division and cancer-related enrichment pathways. TESMIN was associated with high frequencies of somatic mutations and an immunosuppressive tumor microenvironment. Interestingly, patients with elevated levels of TESMIN expression benefited more from commonly used chemotherapy drugs such as cisplatin, paclitaxel, vinorelbine, and docetaxel, whereas those with low levels of TESMIN expression showed favorable clinical responses to immunotherapy.ConclusionAs a prognostic biomarker associated with the cell cycle and immune infiltration, TESMIN may serve as an effective target for predicting the sensitivity to immunotherapy and chemotherapy.
Keywords: prognosis